Highly similar and competing visual scenes lead to diminished object but not spatial detail in memory drawings. Issue 3 (16th March 2022) - Hall, Elizabeth H.; Bainbridge, Wilma A.; Baker, Chris I.
ABSTRACT: Drawings of scenes made from memory can be highly detailed and spatially accurate, with little information not found in the observed stimuli. While prior work has focused on studying memory for distinct scenes, less is known about the specific detail recalled when episodes are highly similar and competing. Here, participants ( N  = 30) were asked to study and recall eight complex scene images using a drawing task. Importantly, four of these images were exemplars of different scene categories, while the other four images were from the same scene category. The resulting 213 drawings were judged by 1764 online scorers for a comprehensive set of measures, including scene and object diagnosticity, spatial information, and fixation and pen movement behaviour. We observed that competition in memory resulted in diminished object detail, with drawings and objects that were less diagnostic of their original image. However, repeated exemplars of a category did not result in differences in spatial memory accuracy, and there were no differences in fixations during study or pen movements during recall. These results reveal that while drawings for distinct categories of scenes can be highly detailed and accurate, drawings for scenes from repeated categories, creating competition in memory, show reduced object detail.